Penulisan Ulang dalam Penerjemahan Berita Daring - Pamungkas, Muhammad Ersan Pamungkas (Kementerian Sekretariat Negara Republik Indonesia, 2017)
Translating online news is a common practice among translators working at government institutions and ministries. Almost all government institutions in Indonesia now have their own official websites and several of them are even available in other languages, particularly English. One of the features of those websites that is usually translated into English is online news articles. Translating online news articles from Indonesian into English poses its own translation difficulties and challenges, including the facts that the original texts (ST) are mostly poorly written, STs that are not clear and sometimes incomprehensible, STs that contain inaccurate data and when those STs have to be translated into English, they have to be ‘modified’ so as to conform to the standard writing of news article in English. Therefore, in this case, a translator has to do more beyond translating. Oftentimes, he has to re-write the articles and produce a proper English news article based on the ST, he has to research missing but important information and he also has to correct incorrect data or information from the original article. Simply put, in the case of translating online news websites, there is blurred line between the concept of ‘translation’ and ‘re-writing’ and this paper tries to investigate whether translating online news articles can be regarded as a ‘pure’ form translation or rewriting. The source of data for this research is taken from news articles of the official website of Cabinet Secretary and their English versions. Several Indonesian articles with their English translations are randomly selected for the analysis of this paper. The result of this paper shows that in many cases of the translation of news article on the website of Cabinet Secretariat, those Indonesian articles are mostly ‘rewritten’ in the Target Text. This paper also concludes that in the case of online news translation, the translator often has to do more than just translating but also rewriting. Keywords: translating, translator, online new article, website, rewriting